Osteopontin targeted theranostic nanoprobes for laser-induced synergistic regression of vulnerable atherosclerotic plaques - Mengqi Xu; Cong Mao; Haoting Chen; Lu Liu; Yabin Wang; Abid Hussain; Sulei Li; Xu Zhang; Ruslan G. Tuguntaev; Xing-Jie Liang; Weisheng Guo; Feng Cao (Acta Pharmaceutica Sinica B, 2022)
Vulnerable atherosclerotic plaque (VASPs) is the major pathological cause of acute cardiovascular event. Early detection and precise intervention of VASP hold great clinical significance, yet remain a major challenge. Photodynamic therapy (PDT) realizes potent ablation efficacy under precise manipulation of laser irradiation. In this study, we constructed theranostic nanoprobes (NPs), which could precisely regress VASPs through a cascade of synergistic events triggered by local irradiation of lasers under the guidance of fluorescence/MR imaging. The NPs were formulated from human serum albumin (HSA) conjugated with a high affinity-peptide targeting osteopontin (OPN) and encapsulated with photosensitizer IR780 and hypoxia-activatable tirapazamine (TPZ). After intravenous injection into atherosclerotic mice, the OPN-targeted NPs demonstrated high specific accumulation in VASPs due to the overexpression of OPN in activated foamy macrophages in the carotid artery. Under the visible guidance of fluorescence and MR dual-model imaging, the precise near-infrared (NIR) laser irradiation generated massive reactive oxygen species (ROS), which resulted in efficient plaque ablation and amplified hypoxia within VASPs. In response to the elevated hypoxia, the initially inactive TPZ was successively boosted to present potent biological suppression of foamy macrophages. After therapeutic administration of the NPs for 2 weeks, the plaque area and the degree of carotid artery stenosis were markedly reduced. Furthermore, the formulated NPs displayed excellent biocompatibility. In conclusion, the developed HSA-based NPs demonstrated appreciable specific identification ability of VASPs and realized precise synergistic regression of atherosclerosis.